SALINE WATER AND NITROGEN FERTILIZATION ON LEAF COMPOSITION AND YIELD OF CORN - Sousa, Geocleber Gomes de (2021)
Absence of drainage associated with high evapotranspiration and irregular precipitations contributes to the accumulation of salts in the soil, reducing nutrient absorption and yield. Nutritional management is important for the crop to express its maximum production potential, and nitrogen is the macronutrient most required by the corn crop. The objective of this study was to evaluate yield and leaf contents in corn under different nitrogen fertilization recommendations and salt stress. The experiment was conducted from June to September 2019, at the University of International Integration of Afro-Brazilian Lusophony in Redenção-CE, Brazil. The experimental design used was completely randomized, in a 2 x 3 factorial arrangement, with 6 replicates, with two levels of electrical conductivity (0.3 dS m-1 and 3.0 dS m-1) and three nitrogen fertilization recommendations (0, 50 and 100% of the recommendation). The variables analyzed were unhusked ear weight, husked ear weight, yield and leaf contents of N, P, K, Ca, Mg and Na. Irrigation with saline water (3.0 dS m-1) reduces the unhusked ear weight, husked ear weight and yield. Nitrogen fertilization recommendations of 50% and 100% promoted higher values of unhusked ear weight, husked ear weight and leaf N contents, but reduced leaf P contents. The 50% and 100% recommendations promote higher yield values for the two levels of electrical conductivity studied (0.3 and 3.0 dS m-1). The 50% and 100% recommendations associated with saline water irrigation increased the leaf contents of K, Na, Mg and Ca.